Pengaruh Profitabilitas Terhadap Harga Saham Manufaktur yang di BEI dengan Perspektif Islam - Wardani, Syandanatama Putri Kusuma; Hidayati, Amalia Nuril (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study is to see the effect of ROA (Return On Asset), ROE (Return On Equity), NPM (Net Profit Margin), and EPS (Earning Per Share) variables on stock price movements in companies listed on the Indonesia Stock Exchange (IDX) in the manufacturing sector of the cosmetics and household needs subsector for the period 2019 to 2021. The population studied included nine companies listed on the IDX during that period. Six companies were selected for this study using purposive sampling technique. Secondary data was collected from the financial statements of six cosmetics and household goods subsector companies which can be accessed through the Indonesia Stock Exchange (IDX) website. This research uses a quantitative approach, associative research type, and panel data regression data analysis tool. According to the conclusion of the study, ROA (Return On Asset) and EPS (Earnings Per Share) have a good and significant influence on stock prices. However, ROE (Return On Equity) and NPM (Net Profit Margin) have no influence on stock prices. The F test shows that ROA, ROE, NPM, and EPS together have a positive and significant effect on stock prices.